Integrin-mediated mTOR signaling drives TGF-β overactivity and myxomatous mitral valve degeneration in hypomorphic fibrillin-1 mice - Gao, Fu; Chen, Qixin; Mori, Makoto; Li, Sufang; Ferrari, Giovanni; Krane, Markus; Fan, Rong; Tellides, George; Liu, Yang; Geirsson, Arnar (The Journal of Clinical Investigation, 2025)
Mitral valve prolapse is often benign, but progression to mitral regurgitation may require invasive intervention and there is no specific medical therapy. An association of mitral valve prolapse with Marfan syndrome resulting from pathogenic FBN1 variants supports the use of hypomorphic fibrillin-1 mgR mice to investigate mechanisms and therapy for mitral valve disease. mgR mice developed severe myxomatous mitral valve degeneration with mitral regurgitation by 12 weeks of age. Persistent activation of TGF-β and mTOR signaling along with macrophage recruitment preceded histological changes at 4 weeks of age. Short-term mTOR inhibition with rapamycin from 4 to 5 weeks of age prevented TGF-β overactivity and leukocytic infiltrates, while long-term inhibition of mTOR or TGF-β signaling from 4 to 12 weeks of age rescued mitral valve leaflet degeneration. Transcriptomic analysis identified integrins as key receptors in signaling interactions, and serologic neutralization of integrin signaling or a chimeric integrin receptor altering signaling prevented mTOR activation. We confirmed increased mTOR signaling and a conserved transcriptome signature in human specimens of sporadic mitral valve prolapse. Thus, mTOR activation from abnormal integrin-dependent cell–matrix interactions drives TGF-β overactivity and myxomatous mitral valve degeneration, and mTOR inhibition may prevent disease progression of mitral valve prolapse.